SERBUK BABAKAN AKASIA SEBAGAI PEREKAT PAPAN PARTIKEL - Suwardi Sumadiwangsa; Sadan Widarmana; Ratmaja Eka Putra; Rozak Memed (Jurnal Penelitian Hasil Hutan, 1988)
This  work  investigates  the use of acacia  (Acacia decurrens Willds.)  bark  powder   mixed   with  paraformaldehyde as an adhesive for particleboard. The treatments included powder  contents  of 10, 12, and 14% of the oven dry  weight basis.  The paraformaldehyde   employed  has also 3 levels i.e. 20, 30, and 40%. Material used for this study  was the jeungjing (Albizia falcataria  (L.) Fosberg.) flakes.   The boards were made in the Forest Products  Research  Centre laboratory  to determine  their physical  and mechanical properties.The effect  of paraformaldehyde  content  alone on the overall particleboards  properties  was not significant.  On the other hand,  the effect  of acacia bark powder  contents  on the particle board properties were significant on water absorption, MOR  and MOE after soaking.  Those qualities were better  with higher powder  content.